Learning how to Learn may Help Children Have a Better Self-Perception (Studia Doctoralia Psychology and Educational Science, 2024)
The present study aims to investigate the differences in primary school students' perception of teachers' teaching methods, as well as their self-perception, as a result of their participation in a teaching program based on the principles of learning how to learn program. A number of 68 primary school students, aged between 7 and 9, M = 8.12, SD = .47, of which 38 were boys and 30 were girls,  participated in the study. Initially, teachers attended a professional training course to acquire these techniques and strategies. After completing the course, the teachers applied the acquired knowledge with students during three school modules, respectively fromJanuary to June 2024. At the beginning and at the end of this period, the students were tested in terms of self-perception but also the extent to which their teachers adopt constructive learning strategies in the classroom (L2L specific). The results showed that teachers' teaching strategies, perceived by the students, improved significantly from the pretest to the posttest, as well as students' self-perception in the areas of school competence, social competence, athletic competence, conduct and self-esteem. Possible relationships between teachers' teaching strategies and approaches to learning on the one hand and students' self-perception on the other were discussed.
Keywords: learning how to learn; self-perception; primary school